Pengungkapan Sustainability Report, Corporate Social Responsibility dan Kinerja Perusahaan terhadap Tax Avoidance - Srikalimah; Santika Mia Grasia; Puji Rahayu (Jurnal Proaksi, 2025)
Main Purpose - The purpose of this discussion is to examine how the disclosure of sustainability reports, corporate social responsibility, and company performance influence tax avoidance. Method - This study utilizes a quantitative approach to explore the interrelationships among the variables under investigation.It relies on secondary data derived from annual reports and sustainability disclosures of mining companies in the mineral sub-sector that are listed on the Indonesia Stock Exchange (IDX) for the period 2021 to 2024. Main Findings - This consideration provides a hypothetical commitment by illustrating that sustainability report disclosure, use of corporate social obligations, and corporate implementation are related to the tendency to avoid taxes, although the direction and significance of the relationship may change. Basically, companies are expected to advance the quality and sharpness of support report disclosure and actualize corporate social obligations in real terms, not just as a convention or image-building effort. Novelty - The researcher focuses on filling the research gap that remains limited in the mineral sub- sector, as well as providing a more specific depiction of how sustainability report disclosure, corporate social responsibility, and company performance influence tax avoidance practices, which have not been previously examined.